A Cluster-Based Approach for the Discovery of Copy Number Variations From Next-Generation Sequencing Data - Liu, Guojun; Zhang, Junying (Frontiers in Genetics, 2021)
The Next-generation sequencing technology offers a wealth of data resources for the detection of copy number variations (CNVs) at a high level of resolution. However, it is still challenging to correctly detect CNVs of different lengths. It is necessary to develop new CNV detection tools to meet this demand. In this work, we propose a new CNV detection method, called CBCNV, for the detection of CNVs of different lengths from whole genome sequencing data. CBCNV uses a clustering algorithm to divide the read depth segment (RDS) profile, and assigns an abnormal score to each RDS. Based on the abnormal score profile, Tukey’s fences method is adopted in CBCNV to forecast CNVs. The performance of the proposed method is evaluated on simulated data sets, and is compared with those of several existing methods. The experimental results prove that the performance of CBCNV is better than those of several existing methods. The proposed method is further tested and verified on real data sets, and the experimental results are found to be consistent with the simulation results. Therefore, the proposed method can be expected to become a routine tool in the analysis of CNVs from tumor-normal matched samples.